Organic Long‐Persistent Luminescence: Many Exciplex Systems Exhibit Organic Long‐Persistent Luminescence (Adv. Funct. Mater. 22/2020). (25th May 2020) - Nishimura, Naohiro; Lin, Zesen; Jinnai, Kazuya; Kabe, Ryota; Adachi, Chihaya
Abstract : In article number 2000795, Ryota Kabe, Chihaya Adachi, and co‐workers show that many exciplex systems exhibit afterglow emission because of the charge separation event during photoexcitation. The emission pathway and color of organic long‐persistent luminescence can be controlled by the relationship between the local excited states and charge‐transfer excited states of materials.